Urea cycle disorders and indications for liver transplantation - García Vega, Marta; Andrade, José D.; Morais, Ana; Frauca, Esteban; Muñoz Bartolo, Gema; Lledín, María D.; Bergua, Ana; Hierro, Loreto (Frontiers in Pediatrics, 2023)
Urea cycle disorders (UCD) are inborn errors of metabolism caused by deficiency of enzymes required to convert nitrogen from ammonia into urea. Current paradigms of treatment focus on dietary manipulations, ammonia scavenger drugs, and liver transplantation. The aim of this study was to describe the characteristics and indication of liver transplantation in UCD in a tertiary hospital. We performed a retrospective study of children with UCD seen in the period 2000-2021. Data was collected on clinical onset, hyperammonemia severity, evolution and liver transplantation. There were 33 patients in the study period, whose diagnosis were: ornithine transcarbamylase (OTC, n=20, 10 females), argininosuccinate synthetase (ASS, n=6), carbamylphosphate synthetase 1 (CPS1, n=4), argininosuccinate lyase (ASL, n=2) and N-acetylglutamate synthetase (NAGS, n=1) deficiency. Thirty one were detected because of clinical symptoms (45% with neonatal onset). The other 2 were diagnosed being presymptomatic, by neonatal/family screening. Neonatal forms (n=14) were more severe, all of them presented during the first week of life as severe hyperammonemia [mean peak 1152 µmol/L]. Seven patients died (6 at debut) and all survivors received transplantation. There was no mortality among the late forms. Of the 27 patients who did not die in the neonatal period, 16 (59%) received liver transplantationwith 100% survival, normal protein tolerance and usual need of citrulline supplementation. The transplant’s metabolic success was accompanied by neurologic sequelae in 69%, but there was no progression of brain damage. Decision of continuous medical treatment in 11 patients appeared to be related with preserved neurodevelopment and fewer metabolic crises.